The Implementation of Motivating Management Function in Local Batik Entrepreneurs: A Case Study on Lesoeng Boutique and Batik Ponorogo - Kurniawan, Galih Puji (CV. Creative Tugu Pena, 2022)
Ponorogo Regency has its own arts and culture which are the characteristics and identity of this Reog City. Batik Ponorogo has a variety of motifs that are unique and different from other regions. This article aimed analyzing the motivation of the owner of the company to establish Lesoeng Butik and Batik Ponorogo business and how to increase motivation to maintain the business of Lesoeng Butik and Batik Ponorogo. The researcher used qualitative method and using documentation, observation in collecting the data. The result show that othe company wants to introduce the Ponorogo batik motif which has its own uniqueness and characteristics compared to other regions in the national and international arena. The motivation of the two company owners is to want to help the government in an effort to preserve batik in Indonesia Keywords: Local Batik Entrepreneurs, Batik Ponorogo. Motivating Management Function